Te Hoe Nuku Roa: A Measure of Māori Cultural Identity - Stevenson, Brendan (He Pukenga Korero: a journal of Māori studies, 2004)
Keywords: ethnic identity; identity; mātauranga māori; tāngata whenua

The Orewa Speech - Crengle, Sue; Pelkowitz, Allan (THE NEW ZEALAND MEDICAL JOURNAL, 2004)

Tiers of Confusion and Blurring Boundaries: Maori, the Local Government Act 2002 and the General Agreement On Trade in Services (Gats) - Bargh, Maria (Political Science, 2004)
In December 2002 a new Local Government Act was passed into statute. Much of the literature, submissions, articles and commentaries leading up to the passing of the Act indicated that a new Act had to clarify the relationships and obligations between local government, the Crown, Maori and the Treaty of Waitangi. In this paper I argue that the new Act has not adequately clarified these relationships and obligations, and that there are particular reasons and consequences arising from this situation. The reasons surround denials from local government that they are the Crown and central government's vested interest in allowing slippage to continue. If we examine the example of the General Agreement on Trade in Services we can see that a failure to clarify the relationships may have detrimental consequences for Maori to protect their rights.
Keywords: crown policy; kāwanatanga; local government; tiriti o waitangi/treaty of waitangi

The Role of Biodiversity in Maori Advancement: A Research Framework. - Harmsworth, Garth (He Pukenga Korero: a journal of Māori studies, 2004)
Keywords: biodiversity; environment; planning; sustainable development

The Problem of Defining an Ethnic Group for Public Policy: Who is Māori and Why Does it Matter? - Kukutai, Tahu (Social Policy Journal of New Zealand, 2004)
Governments in multicultural democracies are increasingly being challenged to justify the collection of ethnic and racial data, and the targeted policies they support. Given mounting opposition to ethnicbased policies in New Zealand, it is timely to consider two questions that have arisen from ongoing debate. The first is what criteria ought to apply to determine who is Mäori for policy purposes. The second is which Mäori ought to benefit from targeted policies and programmes. This paper addresses both questions empirically and makes two suggestions: (1) that statistical and legal definitions of Mäori be amended to take account of both self-identified ethnicity and descent; (2) that programmes which seek to militate Mäori disadvantage be oriented towards those who strongly identify as Mäori, since they are the most likely to be in need.
Keywords: Inequity; data sovereignty; identity; policy; self-identification